HUMAN TRAFFICKING AND MIGRATION: A DEFINING PROBLEM OF THE 21ST CENTURY - Kanali, James (Asian Horizons, 2014)
The consequences and porousness of immigration controls resulting from the multiplicity and fluidity of the structures involved and the resourcefulness of migrant-actors who engage them, have been ambiguous, albeit differently. In this article I argue that controls increase the risks associated with migration which in turn increases the need for migration merchants who are involved in this dubious business. Moreover, more of state control policies indirectly play into the hands of international crime organisations. In addition the political will to curb immigration, buoyed by popular sentiment has had less impact in terms of effective control of cross-border practices in market economy regimes whose borders have remained open to “goods and services.” Nonetheless, the dogma of a border that is open but totally controlled (smart border), would allow each state to act more or less as it sees fit. Bigo argues that coercive measures ostensibly justified by security concerns are often the first to foment insecurity and the very violence it purport to combat.